Comparision of growth of mature all-female and mixed-sex Common carp (Cyprinus carpio L.) stocks in RAS - Kovács, László; Minya, Dániel; Homoki, Dávid; Toviho, Odunayo Abigeal; Molnár, Áron; Fehér, Milán; Stündl, László; Bársony, Péter (Acta Agraria Debreceniensis, 2020)
The common carp (Cyprinus carpio L.) is the most important fish species in Hungary, it is more than 70% of the total Hungarian fish production. The common carp production is important not only just in Hungary but in Middle-East Europe, as well as Southeast Asia. Majority of the production comes from fishpond culture. If the production sector wants to meet the increasing customer demands, there is need to intensify research on the intensive fish production opportunities for example all-female common carp technologies. The all-female technology is one of a genom-manipulation technology. Its production showed better growth rate than mixed-sex population in pond culture. Our experiment combined the recirculation aquaculture system (RAS) and the all-female common carp stocks intensification technologies. The reason for the experiment, is that there are no result about the growth of all-female common carp growth in RAS. The experiment used the „Tatai grey scale type” common carp stocks. We propagated two all-female stocks (T2 and T3) and a control group (TK). Due to technological characteristics of RAS, the water quality parameters were the same for all treatments and corresponded to the technological tolerance of common carp. The experimental period was from July 10, 2019 – November 20, 2019. Result of growth performance showed that the growth of mixed-sex stock was significantly higher than all-female stocks; (Control=3692.0±590.5g, T2=3438.8±415.4g, T3=3294.1±659.1g). Feed conversation ratio (Control=1.3±0.1 T2=1.5±0.2 T3=1.6±0.5) and SGR% (Control=0.8±0.0 T2=0.7±0.1 T3=0.7±0.1) were similar. By the results it can be said the all-female common carp technology has neither advantages nor disadvantages compared to the mixed-sex stock. The all-female technology can be beneficial if the consumers need female common carps. It is worth continuing the experiment and examine how the stocks will perform above 3kg body weight.